Improved Catalytic Activity and Stability of Ba Substituted SrTiO3 Perovskite for Oxidative Coupling of Methane. Issue 19 (16th August 2021) - Wang, Yue; Yang, Xiao; Hou, Chenxiao; Yin, Fumin; Wang, Guowei; Zhu, Xiaolin; Jiang, Guiyuan; Li, Chunyi
Abstract: Perovskite oxides are widely used as the catalyst for oxidative coupling of methane (OCM). The partial substitution of A or B sites in ABO3 perovskites with heteroatoms was effective in improving the catalytic performance, but the promoting mechanism has not been thoroughly studied. In this work, the partial substitution of Sr with Ba in SrTiO3 perovskite was demonstrated to improve both the OCM reaction activity and stability. Compared with SrTiO3 and BaTiO3, the crystal size of Ba0.5 Sr0.5 TiO3 was greatly reduced (∼55 nm), the amount of surface chemisorbed oxygen species acting as the alkaline active centers for OCM was increased, and the electrophilic lattice oxygens with higher electronegativity rapidly replenishing the surface alkaline active sites were obtained. Thereby, a higher C2 yield (∼18 %) and C2 H4 /C2 H6 ratio (∼1.7) were simultaneously achieved. Furthermore, the enhanced reaction stability was attributed to the better thermal resistance of nano‐sized Ba0.5 Sr0.5 TiO3 perovskite. Abstract : Perovskite catalysts : The partial substitution of Sr with Ba in SrTiO3 perovskite not only substantially reduced the crystal size, but also effectively modulated the surface oxygen species and lattice oxygen electronegativity. Thereby, the catalytic activity for oxidative coupling of methane was improved (C2 yield ∼18 %, C2 H4 /C2 H6 ratio ∼1.7), and the reaction stability was also enhanced due to the higher thermal resistance of nano‐crystal.